Assessment of Leadership Style and Safety in Oil and Gas Servicing Firms in Port Harcourt Metropolis, Nigeria - Onuoha, Foreman; Oyegun, Charles U; Ugbebor, John N (International Journal of Occupational Safety and Health, 2021)
Introduction: Safety leadership is the process of interaction between leaders and followers, through which leaders exert their influence on followers to achieve organizational safety goals under the circumstances of organizational and individual factors. Objective: This study was aimed to assess leadership style and safety in oil and gas servicing firms in Portharcourt, Nigeria. Methods: A cross-sectional study was conducted among the junior-staff of the oil servicing firms. The Taro Yamane equation was used to generate appropriate sample size of 389 respondents from 16240 workers. Data analyses was done using analysis of variance (ANOVA). Results: It was established that 230 (59%) respondents agreed that, leaders checked staff work on a regular basis to assess their progress and learning. Many respondents (62%) averred that leaders didn’t gave any incentives for extra work. Also, 338 (87%) respondents adduced that changes in policies were discussed with workers before they were carried out but, the input of the workers were not required, neither staff were expected to be innovative as opined by 76% respondents and leadership emphasis on the importance of quality was sustained. Albeit, workers weren’t allowed to contribute to control standards based on perception of problems. The characteristics of leadership displayed in the companies imply the transactional type. This was because the rapport between workers and leaders wasn’t cordial. Conclusion: The study therefore strongly recommends a review of the leadership style adopted for oil and gas workers in the area, while improving on the worker/leader relationships.